Ramond-ramond central charges in the supersymmetry algebra of the superstring - Berkovits, Nathan [UNESP] (American Physical Society (APS), 1997)
The free action for the massless sector of the type II superstring was recently constructed using closed Ramond-Neveo-Schwarz superstring field theory. The supersymmetry transformations of this action are shown to satisfy an N = 2 D = 10 supersymmetry algebra with Ramond-Ramond central charges.